Determinants of Cash Effective Tax Rate in Energy Sector Companies on the Indonesia Stock Exchange for the Period 2020-2024 - Isna Wati; Yessica Amelia; Ruslaini Ruslaini (Journal of Management and Social Sciences, 2026)
This study aims to examine the influence of capital intensity,  Return on Assets (ROA), liquidity, and company size on the Cash Effective Tax Rate (CETR) as a proxy for tax avoidance in energy sector companies listed on the Indonesia Stock Exchange for the 2020–2024 period. This study uses a quantitative approach with secondary data in the form of annual financial statements. The sample was determined using a purposive sampling technique and obtained 16 companies during five years of observation, resulting in 80 observation data. Data analysis was carried out using multiple linear regression with the help of SPSS 29 software. The analysis stage began with a classical assumption test, then continued with multiple linear regression analysis, as well as hypothesis testing. The results showed that partially capital intensity and ROA had a significant effect on CETR, while liquidity and company size had no significant effect on CETR. Simultaneously, all independent variables had a significant effect on CETR, with a determination coefficient value of 25%.